2004
DOI: 10.1093/intimm/dxh173
|View full text |Cite
|
Sign up to set email alerts
|

In vivo apoptosis of diabetogenic T cells in NOD mice by IFN- /TNF- 

Abstract: Immunization with mycobacterial preparation such as Bacille Calmette-Guerin (BCG) or complete Freund's adjuvant (CFA) prevents the onset and recurrence of type 1 diabetes in non-obese diabetic (NOD) mice. In this study, we explored the mechanism underlying the down-regulation of diabetogenic T cells by BCG treatment. We found that the potential of splenocytes from BCG-immunized diabetic NOD mice to adoptively transfer diabetes was significantly impaired. BCG immunization sequentially induced the production of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 49 publications
4
59
1
Order By: Relevance
“…6). As expected (21,25,53), treatment of wild-type NOD mice with CFA at 5-6 wk of age prevented the development of disease, whereas mice treated with IFA or PBS had no effect on the natural history of disease (Fig. 6A, 6B and data not shown).…”
Section: /2supporting
confidence: 86%
“…6). As expected (21,25,53), treatment of wild-type NOD mice with CFA at 5-6 wk of age prevented the development of disease, whereas mice treated with IFA or PBS had no effect on the natural history of disease (Fig. 6A, 6B and data not shown).…”
Section: /2supporting
confidence: 86%
“…Note, however, that other mechanisms cannot be excluded. Thus, it has been shown that Bacille Calmette-Guerin, CFA (42), or the lymphocytic choriomeningitidis virus (43) may induce protection through IFN-␥-and TNF-␣-mediated T-cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the protection observed after immunotherapy with mycobacterial products [66 _ 69] also depends on IFN-γ response [68] and administration of recombinant IFN-γ inhibits diabetes process in NOD mice [70]. High levels of IFN-γ and TNF-α cytokines following adjuvant immunotherapy could have a role in induction of apoptosis in diabetogenic T cells [67]. The mechanism of adjuvant effect is not restricted to IFN-γ regulation and all changes induced upon adjuvant administration might be primarily under influence of mycobacterial adjuvant-induced alterations in compostion of gut microbiota.…”
Section: Type 1 Diabetesmentioning
confidence: 99%